The wonderful story of henry sugar - Dahl, Roald (Ulverscroft Collections Leicester, 2019)
As fishermen drag a giant sea turtle onto a Jamaican beach, a crowd of tourists lays bids for its meat and shell - until a boy who can talk to animals begs for the creature's freedom. A driver stops to pick up a hitch-hiker - and finds that his passenger is a man of surprising talents. When his plough strikes a hard object, a farm labourer stops and investigates - only to discover a fabulous hoard of buried treasure beneath the soil. And an idle gambler trains himself to see through the backs of playing-cards - then sets off to the casinos